Das Recht der Frau nach dem Bürgerlichen Gesetzbuch : dargestellt für die Frauen - Jastrow, Hermann, 1849-1916 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1897)
The legal rights and responsibilities of women according to the Bürgerliches Gesetzbuch, which entered into effect 3 years after this work was written.